Development of fall detection device using accelerometer sensor - Nur Izdihar, Muhd Amir; Rudzidatul Akmam, Dziyauddin; Norliza, Mohamed; Liza, A. Latiff; Nor Syahidatul Nadiah, Ismail (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper presents the development of Fall Detection System in the form of a wearable device integrating an ADXL335 accelerometer as a fall detection sensor. The system means to detect fall occurrence of the wearer and able to distinguish the activity of daily livings and fall events. In this study, the fall detection system consists of two-part, the transmitter and receiver. Transmitter will be attached to the user’s garment, then the Arduino microcontroller will process the acceleration reading from the sensor and transmit the data via wireless Zigbee networks to the receiver. The receiver which is connected to a computer will display the acceleration graph reading through the monitor. The working hardware of wearable fall detection system in this work is validated through a comparison of data acquisition with previous research, SisFall. The results obtained in this work correspond well to SisFall thus indicate the sensor reliability satisfied the benchmark.